Catastrophic Effects of Out-of-Pocket Payments for Health Care Using Synthetic Panel Data - Adhikari, Shiva Raj; Sapkota, Vishnu Prasad (Economic Journal of Development Issues, 2018)
Panel data can provide more accurate information about the movement of catastrophic payments. The study measures dynamics of catastrophic payment by utilizing recently developed method of creating synthetic panel from two cross-sectional data. It is interested to estimate percentage of households that faced catastrophic health expenditure in first period but didn't face it in second period. Catastrophic payment is defined as OOP payments as a share of total non-food consumption. The threshold for catastrophic health expenditure for non-food expenditure has been set 15% to 50%. The findings related to the movement of households from catastrophic health expenditure to non-catastrophic health expenditure and vice versa between the period of 2004 and 2011. Probability of percentage population faced catastrophic impact due to medicine costs in the first period and in the second period is decreasing from 20.1 per cent to 0.01 percent as increased in threshold 15% to 50%. Similarly, probability of catastrophic impact in the first period but not in the second period is decreasing from 3.1 per cent to 0.00 percent as increased in threshold 15% to 50%. Probability of not having catastrophic impact in the first period but catastrophic impact in the second period is decreasing from 17.2 per cent to 1.9 percent as increased in threshold 15% to 50%. Probability of not having catastrophic impact in both periods is increasing from 60.0 per cent to 98.3 percent as increased in threshold 15% to 50%. Catastrophic to catastrophic incidences in Terai ecological belt are higher than in hills and Mountain. Similarly, Disadvantaged non Dalit Terai caste have higher incidence than other caste groups. Synthetic panel gives the indicative trends; incidences may not be directly comparable with incidences estimated from cross-sectional data. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue, Page: 22-41